Estudo clínico do padrão quantitativo do EEG normal e do coma - Bettero, Paulo Antonio Guimarães (2020)
EEG is a tool frequently used for the diagnostic and prognostic definition of patients with neurological, chronic or acute diseases. Recently, with the advent of digitalization of the exam, it has been possible to expand the analysis of the record, especially based on the quantification of signals. This fact provided the possibility to better evaluate the high frequency and low amplitude electric waves, such as the Gamma and Supergamma waves, both in neurologically normal individuals and in sick patients, especially in those with alterations in consciousness. The objective of this work was to comparatively analyze the electrical signals from the EEGs of two groups of patients, each with 25 individuals, so that one comprised healthy individuals while the other contained patients with altered level of consciousness, admitted to the ICU. The records of each group were analyzed individually with quantifiers in the domain of frequency and time-frequency, then they were compared and subjected to statistical analysis. The results showed wide variation in the power and frequency distribution of electroencephalographic waves between the two groups, with emphasis on the contribution of the Gamma and Supergama waves. In addition, there was a surprising finding: the increasing cranial-caudal increase in VAP means, so that the maximum PCP variation of the medians between the two groups occurred in the posterior region.